Simplify the following expression: 35 + (–13) + (+8) – (–6).
A. 36
B. 50
C. 24
D. 44

35 - 13 + 8 + 6 = 36
So the answer would be D. 36

s

lena.G|Points 231|

Question

Asked 5/18/2013 10:47:02 AM

Updated 3/12/2014 4:04:23 AM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

Rating

There are no new answers.

Simplify this expression: 19 – (–8) – (–14) = ?
A. 25
B. –7
C. 41
D. –3 **Weegy:**
19 – (–8) – (–14)
= 19 + 8 + 14
= 27 + 14
= 41
br> (More)

Question

Updated 2/1/2015 10:57:09 AM

0 Answers/Comments

. Simplify this expression: 13 + (–12) – (–5) = ?
A. –6
B. 30
C. 6
D. –30 **Weegy:** 13 + (–12) – (–5) is 6. (More)

Question

Expert Answered

Updated 3/12/2014 4:04:46 AM

0 Answers/Comments

If 3 times a number minus 2 equals 13, what is the number?
A. 4
B. 2
C. –6
D. 5

Question

Updated 5/18/2013 11:06:42 AM

1 Answer/Comment

If 3 times a number minus 2 equals 13, the number is 5.

3n-2=13

3n=13+2

3n=15

n=15/3

n=5

3n-2=13

3n=13+2

3n=15

n=15/3

n=5

Added 5/18/2013 11:06:42 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [3/12/2014 4:04:52 AM]

Solve the equation: h/ 9
= 7.
A. h = 7/9
B. h = –63 C. h = 1 2/7
D. h = 63 **Weegy:** h/9 = 7, h=7*9, h=63. The answer is D. h = 63 (More)

Question

Updated 3/12/2014 4:04:47 AM

0 Answers/Comments

32,013,111

questions answered

There are no comments.